Cobra. - Galerie Nova Spectra, Den Haag (Den Haag : galerie Nova Spectra, 1981)
Heerup, Henry ; Atlan, Jean-Michel ; Pedersen, Carl-Henning ; Jorn, Asger ; Constant ; Appel, Karel ; Corneille ; Dotremont, Christian ; Doucet, Jacques ; Alechinsky, Pierre ; Reinhoud
Cobra, Galerie Nova Spectra, Den Haag, 14 november - 20 december 1981
boek